PROMOTION OF RIAU TANJAK MALAY SOUVENIRS IN THE RIAU PROVINCIAL TOURISM OFFICE - Anne Khairani; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the promotion of Riau tanjak malay souvenirs in the Riau Provincial Tourism Office. To be able to implementation promotion activities of tanjak needed of a promotion mix so that promotion activities can running well. The promotion mix is divided into 5 namely Advertising, Personal Selling, Publicity, Sales Promotion and Direct Marketing. The promotion of the tanjak is carried out so that the wisdom of the local culture from malay Riau can develop and increase beyond the provinces of Riau. Promotion of tanjak carried out bye the Riau Provincial Tourism Office aimed at the future of tanjak can be know and can become a new creative economy for the people of Riau province. To do promotions of tanjak required understanding of tanjak starting from philosophy, name and type, shape, color and origin of the region of tanjak promoted to the public. This research uses qualitative research methods and to get the data the author uses interview, observation and documentation techniques. From the results of research conducted by the author for 6 months in the Riau Province Tourism Office get the result that the promotion of tanjak continues to increase until it can reach the nomination as the most popular souvenir in the grace of Indonesia and for the development of tanjak already many artisans and communities of tanjak children young in Riau province. Keywords: Promotion Of Riau Tanjak Malay Souvenirs, Promotion Mix,     Enhancement Of Tanjak, Development Of Tanjak.